2014
DOI: 10.5539/ijbm.v9n5p145
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Consumers’ Intention to Use Online Shopping: The Role of Trust

Abstract: Because of online shopping characterized by facelessness and intangibility, consumers are often reluctant to engage in any forms of online transactions (Grabner-Kräuter & Kaluscha, 2003). Accordingly, trust has played a significant role and been considered as a consumers' essential condition to engage in E-commerce. The key objective of this study is to examine the role of trust in Vietnamese consumers' intention to use online shopping through empirically testing the integrated model of trust perspectives whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This means that other parties also have an influence on the desire of SMEs to use this system. The results of this study are consistent with research results [18], [31], and [32]. The results of this study are not consistent with research results from [33].…”
Section: Subjective Norms and Behavioral Intentionsupporting
confidence: 50%
“…This means that other parties also have an influence on the desire of SMEs to use this system. The results of this study are consistent with research results [18], [31], and [32]. The results of this study are not consistent with research results from [33].…”
Section: Subjective Norms and Behavioral Intentionsupporting
confidence: 50%
“…Thevitalpredictorsofadoptionofonlineshoppingare'perceivedeaseofuse'and'perceived usefulness' (Ho & Chen, 2014;Hernandez, Jimenez, & Martin, 2009), Social Influence (Ho & Chen,2014;Venkateshetal.,2003;Weisbergetal.,2011),HedonicMotivation (Davis,Lang,&San Diego,2014;Hsu,Chuan-ChuanLin,&Chiang,2013),choiceandvariety (Srinivasan,Anderson,& Ponnavolu,2002), Convenience(Khareetal.,2012;Wangetal.,2008),Trust(HoandChen,2014Jiang,&Jones,2014)andEnjoyment(Kimetal.,2013Hsuetal.,2012;ChenandTeng,2013).…”
Section: Underpinning Theories and Models Of Adoption Behaviourmentioning
confidence: 99%
“…This research originated from inconsistencies in the results of previous research such as the results of research conducted by Ho and Chen (2014) said there is a significant relationship between trusts to the intention to use, according to him the provider integrity factor significantly affects the intention to use online shop, while different opinions expressed by Chemingui &Lallouna (2013) states that trusts have no significant effect on the intention to use , according to him factors that affect consumer intentions is safety in use is the main one. Then a study conducted by Hasbullah et al (2016) revealed that there is a significant influence between subjective norm on online shopping intentions, the influence of colleagues and friends becomes a major factor, where they spend more time together so as to influence their motivation in behaving, but different results were found from research conducted by Handarkho (2020) which stated that subjective norm has no significant effect on ni at use, but the large number of users who influence the intention of using.…”
Section: Introductionmentioning
confidence: 96%